Kyrk's Theory of Consumption - Dickinson, Z. Clark; Kyrk, Hazel (Quarterly Journal of Economics, 1924)
Kyrk's Theory of Consumption Get access Z. Clark Dickinson Z. Clark Dickinson University of Michigan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 2, February 1924, Pages 343–346, https://doi.org/10.2307/1884017 Published: 01 February 1924